2018
DOI: 10.4097/kjae.2018.71.1.3
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative stroke: pathophysiology and management

Abstract: Although perioperative stroke is uncommon during low-risk non-vascular surgery, if it occurs, it can negatively impact recovery from the surgery and functional outcome. Based on the Society for Neuroscience in Anesthesiology and Critical Care Consensus Statement, perioperative stroke includes intraoperative stroke, as well as postoperative stroke developing within 30 days after surgery. Factors related to perioperative stroke include age, sex, a history of stroke or transient ischemic attack, cardiac surgery (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
33
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(37 citation statements)
references
References 65 publications
(73 reference statements)
0
33
1
Order By: Relevance
“…Such applications include the prevention of perioperative stroke, which occurs in small incidence rate $1-1.9% during noncardiac, nonneurologic, or nonmajor surgery, whereas it increases by 5-to 9-fold in people who undergo high-risk cardiac or brain surgery procedures. 42 Perioperative stroke occurrence rates might go even higher in patients with a thrombosis or other comorbidities. 43,44 Recently, we demonstrated that overexpression of miR-98 and let-7 g resulted in direct targeting and decreased expression of MCP-1 and RANTES cytokines.…”
Section: Discussionmentioning
confidence: 99%
“…Such applications include the prevention of perioperative stroke, which occurs in small incidence rate $1-1.9% during noncardiac, nonneurologic, or nonmajor surgery, whereas it increases by 5-to 9-fold in people who undergo high-risk cardiac or brain surgery procedures. 42 Perioperative stroke occurrence rates might go even higher in patients with a thrombosis or other comorbidities. 43,44 Recently, we demonstrated that overexpression of miR-98 and let-7 g resulted in direct targeting and decreased expression of MCP-1 and RANTES cytokines.…”
Section: Discussionmentioning
confidence: 99%
“…Surgical procedures can cause hemodynamic and inflammatory changes that increase the risk of stroke [3,8]. It has been estimated that embolic events cause more than 60% of perioperative strokes, followed by unknown causes (13.9%), a synergistic effect from hypotension, hypoperfusion and formation of microemboli together (10%), hypoperfusion (9%), hemorrhagic strokes (1%), and the remaining 20% is distributed between other minor and unknown causes [3,6,21]. Surgery also has been known to amplify the inflammatory pathways which can initiate or exacerbate cerebral ischemic injury [3,9].…”
Section: Discussionmentioning
confidence: 99%
“…Surgery also has been known to amplify the inflammatory pathways which can initiate or exacerbate cerebral ischemic injury [3,9]. Perioperative hemorrhagic strokes have been linked to sudden surges of cerebral perfusion; revascularization procedures; for example, can lead to cerebral hyperperfusion syndrome that causes acute neurological deficits [21]. Solid organ transplant surgeries have been previously reported to be associated with different neurological complications; stroke specifically was found to be the most common neurologic complication within the first 30 days after transplant, especially in liver, heart, and lung transplant surgeries [22-24].…”
Section: Discussionmentioning
confidence: 99%
“…Perioperative embolism may originate from intracardiac thrombi, vulnerable atheroma in the aortic arch, or atherosclerotic lesions in large arteries because of manipulation of the above structures during surgery [ 24 26 ]. Intraoperative hypotension may cause watershed infarction in patients with pre-existing large artery steno-occlusive disease [ 27 ]. Most strokes due to these mechanisms are supposed to occur during or immediately after surgery, as shown in a study which found that nearly two thirds of strokes occurred within two days after CABG [ 23 ].…”
Section: Discussionmentioning
confidence: 99%